Direct Tire Recycling: Effect of Sequential Mixing on Rubber Recovery into Malleable Mixture - Rakhman, Moshe Z (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
To achieve optimal mixture properties, the GTR-super-filled NR blend was mixed at mild temperatures to ensure sufficient desulfuration and prevent degradation. The evaluation of fragmentation extent, interfacial adhesion, and unsaturation assesses the evolution of mixture structure. The surface texture of the mixture and related are distinctly improved when a scale-up mixer is used with higher power per unit volume. Comparative semi-quantitative testing validates that visualizing the surface texture is reliable for monitoring the viscosity, interfacial adhesion, cavitation, and elastic memory during mixing. The direct recovery of a super-filled and coarse-graining blend into a processable mixture is achieved through promoted sequential mixing, eliminating the need for a reclaim step.